Negacja społeczeństwa obywatelskiego w totalitaryzmie : kilka refleksji - Blicharz, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The totalitarian polity is basically one of coercion focused on executing a narrow and uncompromising ideological vision by means of mass terror. Setting up any kind of organization is not possible without the acceptance of the state and thus no grass-roots organizations can exist in a totalitarian state. In other words, any form of civil society (understood as both autonomous from the state and capable of generating social capital) is not possible under totalitarianism.
Keywords: totalitaryzm; reżim totalitarny; społeczeństwo obywatelskie; społeczeństwo masowe; społeczeństwo postkomunistyczne